2021
DOI: 10.3390/su13179662
|View full text |Cite
|
Sign up to set email alerts
|

Actions Speak Louder than Words: Investigating the Interplay between Descriptive and Injunctive Norms to Promote Alternative Fuel Vehicles

Abstract: Environmental problems are escalating. Alternate fuel vehicles are a technologically viable solution to curb transport-related pollution and greenhouse gas emissions that cause environmental problems. Based on the theory of norms-driven behavior, this study explains how the underlying facets of subjective social norms (injunctive and descriptive) are linked with personal norms (integrated and introjected) and how this linkage leads to eco-socially conscious consumer behavior related to the choice and use of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 77 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…Injunctive norms represent social norms and refer to the degree to which a specific behavior is commonly accepted or not [42]. It refers to an individual's belief regarding the significant social web around them, and whether they believe that one is complying and abiding by the social pressure [43].…”
Section: Injunctive Social Norms and Green Purchase Intentionmentioning
confidence: 99%
“…Injunctive norms represent social norms and refer to the degree to which a specific behavior is commonly accepted or not [42]. It refers to an individual's belief regarding the significant social web around them, and whether they believe that one is complying and abiding by the social pressure [43].…”
Section: Injunctive Social Norms and Green Purchase Intentionmentioning
confidence: 99%
“…While the sampled companies discussed ethical statements and business activities in their annual reports, for example, compliance with environmental law [67], honest dealing with employees, fair competition [68], and anti-trust laws, this research found that ethical behavior took on a symbolic gesture, and did not find any specific metrics that the sampled companies used to assess their performance. Therefore, the annual report of sampled companies cannot help stakeholders judge their accuracy (GRI P7 Accuracy).…”
Section: Discussionmentioning
confidence: 69%
“…Individuals are driven to enact a certain behaviour by the potential social rewards or punishments associated with this action [ 8 ]. Both types of social norms are well suited to tackle collective action problems, effectively promoting environmental behaviours [ 11 ] such as recycling [ 12 ], reducing public littering [ 8 ], energy conservation [ 13 ], choosing alternate fuel vehicles [ 14 ] and taking climate actions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%